Estrogenic Effects of Tapak Dara (Catharantus roseus) Leaf Methanol Extract on The Estrus Cycle of Adult Female Mice (Mus musculus) Balb/C Strain - Yunita Fatmala; Mahrus Mahrus; Lalu Zulkifli (Jurnal Biologi Tropis, 2022)
Tapak dara plant is a plant that contains several active compounds, such as phenolic acids, flavonoids and alkaloids. The tapak dara plant can act as a sedative, urinary laxative, stop bleeding, and neutralize toxins. In addition, tapak dara leaf extract contains ingredients that can act as antifertilization. This study aimed to determine the effect of methanol extract of tapak dara leaf on the estrus cycle of adult female mice (Mus musculus) Balb/C strain. This research is an experimental research by testing cause and effect. The hypothesis test used in this study was one-way ANOVA and BNT test. The significance value of giving tapak dara leaf methanol extract to female mice showed a significant value so that it can be said that the administration of tapak dara leaf methanol extract caused the estrus cycle of female mice to be longer. The significance value of estrogenic activity in mice shows a significant value of 0.047, so it can be said that estrogen activity also affects the length of the estrus cycle. The results of hypothesis testing using the one-way ANOVA test were significant, so it can be concluded that the methanol extract of tapak dara leaves can cause the estrus cycle of female mice to be longer.